2018
DOI: 10.1007/s00221-018-5295-2
|View full text |Cite
|
Sign up to set email alerts
|

Free choice tasks as random generation tasks: an investigation through working memory manipulations

Abstract: Free choice tasks are tasks in which two or more equally valid response options per stimulus exist from which participants can choose. In investigations of the putative difference between self-generated and externally triggered actions, they are often contrasted with forced choice tasks, in which only one response option is considered correct. Usually, responses in free choice tasks are slower when compared with forced choice task responses, which may point to a qualitative difference in response selection. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 53 publications
1
19
0
Order By: Relevance
“…Moreover, forced choice tasks that require a polar response decision for one or the other response option are differentiated from free choice tasks that require an arbitrary decision between multiple equal response options (e.g., Berlyne, 1957 ). There is a controversy regarding whether forced choice and free choice action modes differ in terms of how actions are selected on the basis of anticipated effects (for findings suggesting differences between the two action modes, see, e.g., Herwig & Horstmann, 2011 ; Herwig et al, 2007 ; Herwig & Waszak, 2009 , 2012 ; Naefgen & Janczyk, 2018 ; Waszak et al, 2005 ; see also Ansorge, 2002 ; Zwosta et al, 2013 , for evidence, suggesting that R–E compatibility effects depend upon the intention to produce an effect; but see e.g., Janczyk, Dambacher, et al, 2015 ; Janczyk, Nolden, et al, 2015 ; Janczyk, Pfister, et al, 2015 ; Janczyk et al, 2017 ; Janczyk, Dambacher, et al, 2015 ; Janczyk, Nolden, et al, 2015 ; Janczyk, Pfister, et al, 2015 ; Pfister et al, 2011 ; Pfister & Kunde, 2013 , for contradictory findings suggesting no difference between forced and free choice). The notion that forced choice actions, in contrast to free choice actions, are stimulus-based and do not depend upon a person's intention or will was already described by Ach ( 1935 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, forced choice tasks that require a polar response decision for one or the other response option are differentiated from free choice tasks that require an arbitrary decision between multiple equal response options (e.g., Berlyne, 1957 ). There is a controversy regarding whether forced choice and free choice action modes differ in terms of how actions are selected on the basis of anticipated effects (for findings suggesting differences between the two action modes, see, e.g., Herwig & Horstmann, 2011 ; Herwig et al, 2007 ; Herwig & Waszak, 2009 , 2012 ; Naefgen & Janczyk, 2018 ; Waszak et al, 2005 ; see also Ansorge, 2002 ; Zwosta et al, 2013 , for evidence, suggesting that R–E compatibility effects depend upon the intention to produce an effect; but see e.g., Janczyk, Dambacher, et al, 2015 ; Janczyk, Nolden, et al, 2015 ; Janczyk, Pfister, et al, 2015 ; Janczyk et al, 2017 ; Janczyk, Dambacher, et al, 2015 ; Janczyk, Nolden, et al, 2015 ; Janczyk, Pfister, et al, 2015 ; Pfister et al, 2011 ; Pfister & Kunde, 2013 , for contradictory findings suggesting no difference between forced and free choice). The notion that forced choice actions, in contrast to free choice actions, are stimulus-based and do not depend upon a person's intention or will was already described by Ach ( 1935 ).…”
Section: Introductionmentioning
confidence: 99%
“…A thorough discussion is beyond the scope of this article (see Gozli, 2019 ). Briefly, recent work suggested that free-choice tasks are essentially random-generation tasks (Naefgen & Janczyk, 2018 ) and exhibit mutual priming effects (e.g., Kiesel et al, 2006 ; Mattler & Palmer, 2012 ; Naefgen, Caissie, & Janczyk, 2017 ). Consequently, forced-choice and free-choice tasks are more and more conceived of in a unified framework instead of reflecting two qualitatively different actions (or action systems; see also Bermeitinger & Hackländer, 2018 ; Naefgen, Dambacher, & Janczyk, 2018 ; Richardson, Pfister, & Fournier, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas reward differences successfully biased choice behavior, choice consistency in the unbiased condition was highly variable. It is possible that this behavior depended on the individual strategy with some participants aiming at balanced or random choice behavior [34] while others strategically selected one target they would prefer throughout a block. However, answers given by participants during debriefing suggested that unbiased choice behavior are most likely not explained by conscious strategies: When asked for specific strategies during choice-trials, only one participant noted he/she tried to choose both targets equally often, and two stated they always aimed to select the same choice target.…”
Section: Discussionmentioning
confidence: 99%